PENGARUH TERPAAN KONTEN TIKTOK @ANAKBUKDANI TERHADAP MINAT BELI PRODUK MAKANAN PADA FOLLOWERS - Anisa Febriyanti; Intan Kemala; Umar Abdur Rahim (STAI DI AL-HIKMAH, 2026)
This study aims to determine the effect of exposure to TikTok content from the account @anakbukdani on followers’ purchase intention toward food products. The rapid growth of TikTok as a social media platform has encouraged the emergence of culinary content creators who influence consumer behavior through visual and persuasive content. This study employed a quantitative approach with an associative research design. The population consisted of 113,400 followers of the TikTok account @anakbukdani. A sample of 100 respondents was selected using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using simple linear regression with SPSS. The results showed that exposure to TikTok content has a positive and significant effect on purchase intention. The significance value obtained was 0.000, which is lower than 0.05. Furthermore, the coefficient of determination (R²) was 0.792, indicating that 79.2% of the variation in purchase intention is explained by exposure to TikTok content, while the remaining 20.8% is influenced by other factors outside the study. These findings confirm that the frequency, duration, and attention given to TikTok culinary content significantly contribute to increasing followers' purchase intention toward food products.